Sedimentary processes and cold-water coral mini-mounds at the Ferrol canyon head, NW Iberian margin. (December 2018) - Collart, Tim; Verreydt, Wencke; Hernández-Molina, F. Javier; Llave, Estefanía; León, Ricardo; Gómez-Ballesteros, María; Pons-Branchu, Edwige; Stewart, Heather; Van Rooij, David
Highlights: Sedimentary processes in the Ferrol canyon head are affected by bottom currents. Bottom currents result from MOW and internal tide interaction with the canyon head. Relict CWC mini-mounds occur upslope from favourable conditions in the canyon head. Pockmarks provided preferential colonization surfaces for CWC mini-mound initiation. An early Holocene shift of the ENACW-MOW interface is proposed based on CWC mini-mounds. Abstract: The western Iberian margin has a complex morphology controlled by both geological and oceanographic processes. Compared to the submarine canyons in the southern part of this margin (e.g. Nazaré and Setubal), the canyons in the northern part (e.g. Ferrol and A Coruña) have received little attention. This study maps the geomorphological features around the Ferrol canyon head and combines them with oceanographic observations to infer the sedimentary and oceanographic processes active in this area. Furthermore, the occurrence of a cold-water coral (CWC) mini-mound province near the canyon head and the Ortegal Spur pockmark field is investigated with regard to seepage processes, oceanographic conditions and anthropogenic impact. The Ferrol canyon head and outer Ortegal Spur are characterized by erosional (erosional and abraded surfaces, contourite channels and furrows), depositional (contourite drifts and sediment waves) and mixed (contourite terrace) features, indicating a dominant control of bottom currents on the sedimentary processes. Bottom currents are related to the interaction of the canyon head topography with both the Mediterranean Outflow Water (MOW) slope current and with M2 internal tides associated to the interface (pycnocline) between Eastern North Atlantic Central Water (ENACW) and MOW. Due to this interaction, the Ferrol canyon head is subject to active sediment resuspension and forms a potential source area for the intermediate nepheloid layers along the NW Iberian upper slope. The CWC mini-mounds (1.9–2.7 m high and 75–141 m in diameter) occur between 400 and 560 m depth. Seismic facies signatures indicative of fluid-flow and morphometric analysis implies that larger CWC mini-mounds adjacent to the pockmark field initiated by colonization of pre-existing pockmarks, while smaller more clustered mounds developed independently. The observed mini-mounds are relict features likely related to their position outside of the contemporary ENACW-MOW interface which favours CWC growth through (1) increased bottom currents, enhancing food supply and (2) the presence of a potential density envelope σθ = 27.35–27.65 kg/m 3, proposed to control coral larvae transport along the NE Atlantic margin. Alternatively, the lack of contemporary coral growth might be related to habitat destruction by bottom trawling. However, a preliminary age constraint reveals CWC growth occurred during the early Holocene, coeval to relict CWC mini-mounds near canyon heads on the Armorican margin. Their existence suggests a regional shift in the NE Atlantic density profile where the ENACW-MOW interface occurred up to 200 m above its contemporary position.